Alarming Mortality of Biliary Atresia in Two Senegalese Tertiary Hospitals: A Plea For Early Diagnosis - Ibrahima Bocar Wellé; Pape Alassane Mbaye; Ndeye Aby Ndoye; Faty Balla Lo; Ndeye Fatou Seck; Doudou Gueye; Dior Ndiaye; Florent Tshibwid A Zeng; Aminata Mbaye; Oumar Ndour; Gabriel Ngom (European Scientific Journal, ESJ, 2022)
Background: The management of biliary atresia is challenging in low-income countries, with delayed diagnosis and its consequences. We aimed to report its epidemiological, diagnostic, therapeutic aspects and outcomes in Dakar, Senegal.Methods: We conducted a 5-year retrospective review, which included 16 patients, admitted in the pediatric surgery services of Aristide Le Dantec University Teaching Hospital and Diamniadio Children's Hospital.Results: The mean age at admission was 105.6 (1 - 420 days), with 10 girls. Cholestatic jaundice was found in all cases, discolored stools in 43.7%, dark urine and hepatomegaly in 31.2%.  All patients had biological cholestasis and cytolysis syndromes. The ultrasound was performed in all patients with a sensitivity of 56.2%.  The mean age at the time of surgery was 145 days (22 – 540 days). The surgical exploration was conducted in 10 cases and found type IV Biliary Atresia in 50%. The Kasai procedure was performed in 4 cases and liver biopsy in 9 cases.  Mortality occurred in 75% (50% post-operatively and 25% pre-operatively). In two cases, the postoperative course was unremarkable with the success of the Kasai Procedure after a 42-months follow-up. Two patients were lost to follow-up.Conclusion: Biliary atresia still has high mortality in our context. This is mainly due to delayed diagnosis, which is common in our environment. Multidisciplinary assessment of persistent neonatal jaundice is crucial to reduce biliary atresia-related mortality